The effect of empathy to bystander's role towards bullying at school through moral disengagement as a mediator - Yayah Durrotul Gholiyah; H. Fuad Nashori; Raden Rachmy Diana (Communications in Humanities and Social Sciences, 2021)
This study aims to illustrate the effect of empathy on the role of the bystander towards bullying at school through moral disengagement as the mediator. Moral disengagement affects bystanders' role. In this case, an outsider or ignorant bystander indicates higher moral disengagement than a defender or defensive bystander. The subject were 245 high school students in the age of 15-17 years. The respondents acted as bystanders adapted from the Participant Role Questionnaire (PRQ) scale.Â  The researcher adopted the Basic Empathy Scale dan Moral Disengagement Scale as the measuring instrument. The data analysis employed a simple mediation analysis technique with bootstrapping method. The results indicated that first, there was a positive and significant effect of empathy on the role of defender bystander mediated by moral disengagement. Second, there was a negative and significant effect of empathy on reinforcer bystander's role towards bullying at schools as mediated by moral disengagement. Third, the study also indicated that there was no effect of empathy to the bystander's roles as an assistant, outsider, and aggressive defender through moral disengagement as a mediator. One of implications for future interventions in schools, for instance, bystander training emphasizing an effective way to act towards bullying at school.